2021
DOI: 10.1186/s12951-021-01022-z
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles derived from CD73 modified human umbilical cord mesenchymal stem cells ameliorate inflammation after spinal cord injury

Abstract: Background Spinal cord injury (SCI) is an inflammatory condition, and excessive adenosine triphosphate (ATP) is released into the extracellular space, which can be catabolized into adenosine by CD73. Extracellular vesicles have been designed as nano drug carriers in many diseases. However, their impacts on delivery of CD73 after SCI are not yet known. We aimed to construct CD73 modified extracellular vesicles and explore the anti-inflammatory effects after SCI. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 67 publications
0
31
0
Order By: Relevance
“…Adenosine signaling may contribute to the immunomodulatory activity of EVs via the conversion of AMP to adenosine by the GPI-anchored 5′-ecto-nucleotidase CD73 present on enriched UC-MSC EVs (Priglinger et al, 2021 ). A recent report by Zhai et al ( 2021 ) demonstrated that the use of EVs produced by virus-transformed hUC-MSC engineered to increase the levels of CD73 alleviated inflammation after SCI in a mouse model, and regulated macrophage polarization in vitro . Along the same line, Xu et al ( 2018 ) demonstrated that CD73-deficient mice displayed overwhelming immune responses and poor locomotor recovery after SCI.…”
Section: Discussionmentioning
confidence: 99%
“…Adenosine signaling may contribute to the immunomodulatory activity of EVs via the conversion of AMP to adenosine by the GPI-anchored 5′-ecto-nucleotidase CD73 present on enriched UC-MSC EVs (Priglinger et al, 2021 ). A recent report by Zhai et al ( 2021 ) demonstrated that the use of EVs produced by virus-transformed hUC-MSC engineered to increase the levels of CD73 alleviated inflammation after SCI in a mouse model, and regulated macrophage polarization in vitro . Along the same line, Xu et al ( 2018 ) demonstrated that CD73-deficient mice displayed overwhelming immune responses and poor locomotor recovery after SCI.…”
Section: Discussionmentioning
confidence: 99%
“…The overexpression of HIF in MSCs-exosomes exerted a better proangiogenic effect in cranial defects [ 138 ], myocardial infarction [ 139 ], and early ischemic necrosis of the femoral head [ 140 ]. A recent study found that CD73-modified MSC-derived EVs could break down overreleased adenosine triphosphate (ATP) and improve the M1 to M2 polarization phenotype of microglia, thereby improving locomotion in mice with spinal cord contusion [ 141 ].…”
Section: Engineering Msc-derived Exosomes For Improving Therapeutic P...mentioning
confidence: 99%
“… 140 To date, the accumulated evidence confirms that MSCs can skew the balance between M1/M2 macrophages towards the M2 phenotype, thereby facilitating functional neurological improvement post-SCI. 141 , 142 …”
Section: Contribution Of Mscs Transplantation To Sci Prognosismentioning
confidence: 99%
“…140 To date, the accumulated evidence confirms that MSCs can skew the balance between M1/M2 macrophages towards the M2 phenotype, thereby facilitating functional neurological improvement post-SCI. 141,142 Study investigating the mechanism involved found that this effect was associated with some soluble factors secreted by MSCs. 134 Stimulated MSCs can significantly secrete numerous cytokines including TGF-β, indoleamine 2,3-dioxygenase (IDO), prostaglandin E2 (PGE2), IL-4, and IL-6 following stimulation by inflammatory mediators.…”
Section: Mscs For Sci: Macrophage-mediated Neuroinflammationmentioning
confidence: 99%